TYPIFICATION OF SRI LANKAN GESNERIACEAE. (20th February 2019) - Ranasinghe, S.; Middleton, D. J.; Atkins, H. J.; Milne, R.; Möller, M.
Abstract : Towards a comprehensive revision of Gesneriaceae in Sri Lanka, 12 names are here typified, of which 11 are lectotypifications, including one second-step lectotypification, and the other is a neotypification.